2020
DOI: 10.1021/acs.inorgchem.0c01537
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Construction of (3,6)-Connected rtl, ant, and Chiral anh Nets Based on Structural Investigation of Several MOFs via Steric Tuning of Linkers

Abstract: Six cobalt–organic frameworks (1–6) were solvothermally constructed with a tritopic pyridine-carboxylate linker (L-H) and its methyl- and methoxy-functionalized derivatives (L-OCH3 and L-CH3). Due to incorporated multiple substituents with various steric hindrances, the tritopic linkers adopt different molecular configurations, Y-shaped and T-shaped, which further combine octahedral or trigonal-prismatic inorganic nodes to afford diverse (3,6)-connected nets. Consequently, 1 and 2 are rtl nets and 3 and 4 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…27 As a scarce type, the ant network with the point symbol (4 2 •6) 2 (4 4 •6 2 •8 8 •10), on behalf of the topology about the inorganic compound of anatase (TiO 2 ), is constituted of 3,6-connected nodes and has been previously discovered in phosphates and abundant MOF structures. 28,29 These ant-type MOFs also have been explored in the fields of gas separation, fluorescence, and magnetism. 30−33 However, as far as we know, there are rarely reported instances of a linear dicarboxylic ligand as a PPA and no precedents based on the ant-type MOF platforms to implement PSP so far.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 As a scarce type, the ant network with the point symbol (4 2 •6) 2 (4 4 •6 2 •8 8 •10), on behalf of the topology about the inorganic compound of anatase (TiO 2 ), is constituted of 3,6-connected nodes and has been previously discovered in phosphates and abundant MOF structures. 28,29 These ant-type MOFs also have been explored in the fields of gas separation, fluorescence, and magnetism. 30−33 However, as far as we know, there are rarely reported instances of a linear dicarboxylic ligand as a PPA and no precedents based on the ant-type MOF platforms to implement PSP so far.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, the vast majority of PSP MOFs were derived from the insertion of C 3 -symmetric pore-partitioning agents (PPAs) into classical MOF platforms (acs topology) to achieve the purpose of PSP, such as FJU-90, the CPM-33 family, and the trz-pacs-D family . As a scarce type, the ant network with the point symbol (4 2 ·6) 2 (4 4 ·6 2 ·8 8 ·10), on behalf of the topology about the inorganic compound of anatase (TiO 2 ), is constituted of 3,6-connected nodes and has been previously discovered in phosphates and abundant MOF structures. , These ant-type MOFs also have been explored in the fields of gas separation, fluorescence, and magnetism. However, as far as we know, there are rarely reported instances of a linear dicarboxylic ligand as a PPA and no precedents based on the ant-type MOF platforms to implement PSP so far. To further enrich the variety of PPAs and make the best of an extant classic topology platform to realize novel porous MOFs, herein, we propose an embedding metal-carboxylate chain-induced topology upgrade (ECTU) strategy to realize topology evolution and segmentation of the pore space inspired by documented excellent works.…”
Section: Introductionmentioning
confidence: 99%
“…Single-crystal X-ray diffraction data revealed that they also crystallize in tetragonal space group P 4 3 2 1 2 and are isostructural MOFs of NJTU-Bai79 with the metal ion changed. Notably, these MOFs are the first series of (3,6)-connected ant topological MOFs to be constructed from [Fe 2 M­(μ 3 –OH)­(COO) 6 (pyridyl) 2 ] clusters and the ligand containing both the pyridyl group and −COO groups. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Based on the above concerns and as a continuation of our research into the design and construction of diverse MOFs for multifunctional applications, in this work, an exceptionally stable luminescent framework, [Tb 4 L 2 (HL)­(HCOO)­(H 2 O) 2 ]·9H 2 O·DMF ( Tb-MOF ), was successfully fabricated with an amide-functionalized tetracarboxylate ligand (5-(3,5-dicarboxybenzamido) isophthalic acid) (H 4 L) and Tb­(NO 3 ) 3 ·6H 2 O under hydrothermal conditions. Structural analysis shows that Tb-MOF s possessed a three-dimensional (3D) framework based on a two-dimensional (2D) double–decker layer linked by H 4 L ligands and formate anions.…”
Section: Introductionmentioning
confidence: 99%